Nonlinear numerical simulation for reinforced concrete elements with explicit time integration procedure - B. Abdelwahed (Case Studies in Construction Materials, 2020)
This study aims to assess numerically the behavior of a wide range of reinforced concrete (RC) components under bending or combined effect of bending and axial compression. Reference case studies of RC beams with different reinforcement ratios and beam-column joints are modeled using LS-DYNA software. When larger time step is used in modeling with implicit solvers, convergence problems may appear at higher degrees of nonlinearities, as the solution is reached through multiple iterations to reach equilibrium at every time step. To avoid these divergence issues, explicit time integration procedure is another alternative and can be used effectively in simulating dynamic problems. With minimizing inertia effects, this procedure can also be used to solve static and quasi static problems. In this study, explicit time integration procedure is utilized and the acting loads were applied slowly to minimize the inertia effects. Consequently, longer run time for the simulation process is needed with explicit time integration. Selective Mass Scaling (SMS) can be used to control the required run time by increasing the model critical time step by adding artificial mass to a limited number of stiff elements like, the transverse reinforcements. With this procedure, similar results to the reference experimental findings are obtained in terms of load-displacement curves, crack patterns and strains in the reinforcements. Models verification with different added masses are shown using grid convergence index (GCI) method. The main objective of this work, is to assess the accuracy of explicit solvers in modeling RC elements under quasi static loading. So that, they may be used with confidence for modelling different RC elements.